Volume change study due to moisture variation related to different sources - A. Khalil, Amina (International Journal of Engineering and Technology, 2018)
Volume change in the soil mass due to variation in moisture change may cause several problems and severe damages, especially to the lightweight structures. In this study, numerically volume change caused by variation in moisture content (heave and settlement) around a selected building would be studied using Geo-Studio software. Different types of flowing water resources that cause volume changing to the soil were used. These types are a seasonal wetting-drying effect, surface rainfall, pipe leaking, and infiltrations from the septic tank. In addition four types of soils (having different clay content) which denoted as (S1, S2, S3, S4)* were used in this research work. For speci-fied water resource, the water variation for the selected sources was simulated using SEEP/W and then using SIGMA/W to compute the heave and settlement. Several laboratory tests were conducted to obtain the soil parameters that would be used in the numerical analysis. The laboratory tests include the index, compaction, permeability (saturated/unsaturated), compressibility and soil-water characteristic curve tests. Most of the obtained properties for the soils were used in the finite element simulations. Results showed that the wetting-drying due to sea-sonal rise and existence of septic tank give a significant effect on the soil heave and settlement when compared with other studied sources. For the infiltration case, the influence zone was in the first-meter depth of the soil mass. Thickness variation (DH) effect extends outside the edge of the building to about 11-15 m for wetting-drying cases, while its values extend about 12.5 m for other sources. During the initial period, the settlement rate was clearly higher in soil types S4, and S3 than S2, and S1 soils.* S1: CH soil, S4: SM Soil, S2: 80%CH & 20%SM, S3: 20%CH+80%SM.Â Â